REMOTELY INNOVATIVE innovation in a hybrid/remote& ai driven world. - Coughlan, Tom (College teacher) (ROUTLEDGE, 2025)
In the near term, the future will not belong to AI, but it will belong to the people who understand AI and how to strategically leverage its advantages.This book gives managers a new perspective on innovation and AI-allowing them to seize the future. As the pace of change has increased, organizations have needed to invest in innovation initiatives to survive and thrive. Up until now, these models have focused on co-location, which is no longer an option in some cases and may not be necessary for all, leaving organizations scrambling for options. Following up on their work in Managing at a Distance, Tom Coughlan and David Fogarty have developed this guide to help managers navigate the challenges of innovation in a world of hybrid and remote workers amidst the ever-increasing use of AI. They tackle questions such as the difference between creativity and innovation and how proximity (or lack of it) impacts teams, and present strategic, structural, and measurement solutions to maximize the role of AI in successful innovation while not minimizing the people who make up organizations.Platform-agnostic, this book will appeal to organizational leaders and managers who work with knowledge workers of any type, as well as students and instructors in graduate business courses, executive education, and corporate training programs.